Examining the relationship between household wealth and colorectal cancer screening behaviors among U.S. men aged 45–75. (September 2022) - Korous, Kevin M.; Cuevas, Adolfo G.; Chahoud, Jad; Ogbonnaya, Uchenna C.; Brooks, Ellen; Rogers, Charles R.
Abstract: Colorectal cancer (CRC) is the third leading cause of cancer-related death among men in the United States (U.S.), particularly among men aged 45 years and older. Early-detection screening remains a key method of decreasing CRC-related deaths, yet socioeconomic barriers exist to planning and completing CRC screening. While accumulating evidence shows income disparities in CRC screening prevalence, a dearth of research has investigated wealth disparities. This study aimed to determine whether household wealth was associated with CRC screening uptake and future screening intent. In February 2022, we sent an online survey to potential participants; U.S. men aged 45–75 years were eligible to participate. We examined four CRC screening behaviors as outcomes: ever completing a stool-based or exam-based screening test, current screening status, and future screening intent. Household net wealth, determined by self-reported household wealth and debt, was the primary predictor. We used logistic regression to estimate odds ratios (ORs) and their 95% confidence interval (CI). Of the study participants ( N = 499), most self-identified as Non-Hispanic White, were aged 50–64 years, and had previously completed a CRC screening test. Results revealed that, among men aged 45–49 years, higher net wealth decreased the odds of ever completing a stool- or exam-based test (OR = 0.58, 95% CI: 0.33, 0.98; OR = 0.55, 95% CI: 0.31, 0.94, respectively). By contrast, among men aged 50–75 years, higher net wealth increased the odds of being current with CRC screening (OR = 1.40, 95% CI: 1.03, 1.92). Net wealth was unassociated with CRC screening intent. These findings suggest that household net wealth, rather than income, is an important socioeconomic factor to consider in relation to uptake of CRC early-detection screening. The financial and social cognitive mechanisms linking household wealth to CRC screening behaviors merit future research and intervention. Highlights: Wealth was associated with U.S men's adherence to screening for colorectal cancer. Age modified the association between wealth and colorectal cancer screening uptake. Wealth reduced the odds of past colorectal screening completion for men 45–49 years.